Pengaruh Perceived Risk dan Herding Behavior terhadap Intensi Berinvestasi dengan Covid-19 sebagai Variabel Pemoderasi - Dian Agustina; Atik Ul Mussanadah; Destya Winda Kholifah; Sarniati Sarniati (Global Financial Accounting Journal, 2022)
Purpose – This study aims to examine the effect of COVID-19 on investment intentions, the effect of perceived risk and herding behavior on investment intentions, and the effect of perceived risk and herding behavior on investment intentions moderated by COVID-19. Research Method - This research was conducted on individuals who have invested using purposive sampling. The number of samples obtained is 56 investors who invest in the capital market. The data were analyzed using SPSS version 25. Findings - The results showed that perceived risk and herding behavior had a positive effect on investment intentions and COVID-19 moderated the relationship between herding behavior and investment intentions, but on the other hand, COVID-19 did not moderate the relationship between perceived risk and investment intentions. Implication - This research is expected to contribute to improving the behavioral literature on financial markets related to the influence of perceived risk, herding behavior on investment intentions by adding COVID-19 as a moderating variable and to fill research gaps on investment interest during the COVID-19 pandemic in Indonesia which has not been widely studied. The results of the study can be used as consideration for stakeholders to increase individual investment intentions in the capital market by better understanding investor behavior, especially during the COVID-19 pandemic and the transitional period of economic recovery.